Necessary Nerve Fatigue - F. Todd Goodson (Educational Considerations, 2020)
A major transformation of a core academic school subject will undoubtably ripple through society in ways we are not currently equipped to map. What we can do, however, is pay much more attention to those shining moments of innovation in our history as educators. Returning to the primary documents and reports from the time can help any number of ways. Rarely are we reinventing the wheel, even if we naively assume we are. Large widespread curricular movements such as the English elective programs do not magically appear. They emerge from a larger cultural, intellectual, pedagogical, and economic environment. It is always instructive to go back and examine those moments in schooling, as they are ripe with lessons. Certainly interesting and often powerful methods and methodologies can be found, but the dynamics leading to the creation of widespread curricular innovation are endlessly fascinating.
Keywords: historical research